Conversion‐Type MnO Nanorods as a Surprisingly Stable Anode Framework for Sodium‐Ion Batteries. (29th March 2020) - Wang, Shitong; Dong, Yanhao; Cao, Fangjun; Li, Yutong; Zhang, Zhongtai; Tang, Zilong
Abstract: The emergence of nanomaterials in the past decades has greatly advanced modern energy storage devices. Nanomaterials can offer high capacity and fast kinetics yet are prone to rapid morphological evolution and degradation. As a result, they are often hybridized with a stable framework in order to gain stability and fully utilize its advantages. However, candidates for such framework materials are rather limited, with carbon, conductive polymers, and Ti‐based oxides being the only choices; note these are all inactive or intercalation compounds. Conventionally, alloying‐/conversion‐type electrodes, which are thought to be electrochemically unstable by themselves, have never been considered as framework materials. This concept is challenged. Successful application of conversion‐type MnO nanorod as a anode framework for high‐capacity Mo2 C/MoO x nanoparticles has been demonstrated in sodium‐ion batteries. Surprisingly, it can stably deliver 110 mAh g −1 under extremely high rate of 8000 mA g −1 (≈70 C) over 40 000 cycles with no capacity decay. More generally, this is considered as a proof of concept and much more alloying‐/conversion‐type materials are expected to be explored for such applications. Abstract : Successful application of conversion‐type MnO nanorods as a super‐stable anode framework for high‐capacity nano‐Mo2 C/MoO x in sodium‐ion batteries is demonstrated. This challenges the conventional consensus that conversion‐/alloying‐type electrode materials cannot be used as stable hosts and opens up a new door to the designing of hierarchical architectures.